Neurexin-3a IgG-mediated autoimmune encephalitis: a case report and literature review - Wang, Pin; Sun, Lin; Wei, Yan; Cheng, Ling; Cheng, Haoyang; Shi, Peiyu; Xu, Yingying (Frontiers in Immunology, 2025)
We summarized the clinical manifestations, auxiliary examinations, treatment, and prognostic characteristics of a patient with neurexin-3a IgG-mediated autoimmune encephalitis. On March 2, 2024, a 43-year-old male patient was admitted to the Second Hospital of Shandong University and had prodromal symptoms of infection before the onset of encephalitis. The main manifestations were episodic loss of consciousness, eyes turned upward to the right, clenched teeth, bleeding from tongue bite, and limb twitching. Imaging results showed that the left frontal lobe was characterized by a patchy, slightly longer T1 and T2 signal foci, with a slightly higher signal in the pressurized water image. The CSF virus test was normal; both the serum and CSF were positive for neurexin-3a antibodies using CBA, which were confirmed by TBA. The patient’s symptoms improved after glucocorticosteroid therapy. Neurexin-3a IgG-mediated autoimmune encephalitis is a new type of autoimmune encephalitis, and suspicion of associated disease requires further testing for neurexin-3a IgG for a definitive diagnosis.